On non-Kupka points of codimension one foliations on ℙ3 - CALVO-ANDRADE,OMEGAR (2016)
Abstract We study the singular set of a codimension one holomorphic foliation on ℙ 3 . We find a local normal form for these foliations near a codimension two component of the singular set that is not of Kupka type. We also determine the number of non-Kupka points immersed in a codimension two component of the singular set of a codimension one foliation on ℙ 3.